Mindfulness Skills Training and Psychological Skills Training Impact on Psychological Factors and its Impact on Athletic Performance: A Case on Saudi Arabia Athletes - Dr. Muhammad Awais Bhatti , (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
The purpose of the present study was to evaluate the effect of mindfulness and psychological skills training on Saudi Arabian athletes' athletic performance via psychological aspects. Using a convenient sampling technique, applied cross-sectional study, quantitative research approach, and structural equation modeling, a sample of 350 athletes participated (SEM). According to the survey, mindfulness and psychology skills training significantly and favorably improved athletic performance via psychological aspects. In particular, mindfulness skills training considerably enhanced psychological variables such as attention, concentration, and emotional regulation, whereas psychological skills training greatly enhanced psychological factors. This research has significant implications for athletes, coaches, and sports psychologists in Saudi Arabia, stressing the significance of incorporating mindfulness and psychological skills training into sports psychology to improve athletic performance. Future studies should investigate the impact of mindfulness and psychological skills training on sports performance in various cultural contexts using more significant sample numbers and control groups.